Improved Diet Quality in Elite and Entry-Level Military Women Compared With Civilian-Matched Counterparts - Tyler E Oliver; Soothesuk Kusumpa; Laura J Lutz; James P McClung; Holly L McClung (Current Developments in Nutrition)
Background: Dietary intake is a modifiable factor linked to short-term and long-term health. The Healthy Eating Index (HEI) is an objective measure to assess diet quality and population-level comparisons, like military to civilian. Objectives: This study aimed to characterize diet quality of early-career and mid-career female soldiers compared with that of age-matches and sex-matched civilians and to link indicators of cardiometabolic disease risk to dietary outcomes and health status. Methods: This is a retrospective, cross-sectional assessment of HEI-2020 scores with cardiometabolic profiles of female elite warfighters (FEWs) and basic combat trainees using Block food frequency questionnaires and blood biomarkers. FEW (n = 13; 30 ± 6 y, mean ± SD) and graduates of elite combat training and basic combat training (BCT; n = 150, 21 ± 4 y) from Ft. Sill, Oklahoma, with stratified (time, sex, and age) civilian data (NHANES) were compared. The Mann–Whitney–Wilcoxon rank sum and Kruskal–Wallis tests were used to assess group differences. Weights, strata, and primary sampling units were used to account for NHANES sampling design, with FEW and BCT subjects assigned a weight, strata, and primary sampling unit of 1. Nonplausible reporters identified as women reporting an energy intake of <300 or > 4500 kcal/d were excluded from the analysis. Results: Mean HEI-2020 scores were greater in both FEW and BCT than those in NHANES groups (FEW: 67 ± 11 compared with 48 ± 15; pre-BCT: 60 ± 12 and post-BCT: 68 ± 11 compared with 50 ± 13). Diet quality for military groups were greater in 11 of the 13 HEI components than those for NHANES groups. Biomarkers associated with cardiometabolic disease risk (lipid profile, glucose, and insulin) improved in FEW and BCT compared with that in NHANES groups. Conclusions: FEW consumes a healthier diet than BCT and civilian women. Outcomes suggest the military nutrition environment promotes female warfighter health and warrants further research for understanding the impact of diet associated with long-term health outcomes.